2018
DOI: 10.1002/ange.201808578
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Alkyne Analogue of the de Mayo Reaction: Synthesis of Medium‐Sized Carbacycles and Cyclohepta[b]indoles

Abstract: Embedded medium-sized carbacycles and cyclohepta [b]indoles occur frequently as scaffold elements in natural products and bioactive compounds.Described herein is ac onceptionally novel photochemically triggered cascade process to these scaffolds.K ey to the cascading ring-expansion process is an unprecedented intramolecular alkyne analogue of the de Mayor eaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…As we had postulated the formation of enaminone (assisted by catalytic amounts of formic acid) that was generated in situ during the course of the photoreaction (Scheme 1), we independently synthesized the enaminone by thermal method. 27,28 Analysis of the enaminones derived from the thermal reaction of cyclic β-diketones 1/2 with o-vinlyanilines 3a-c showed that the endocyclic enaminone-8 was favored over exocyclic enaminone-9 for 2-acetylcyclohexanone 1, while the exocyclic enaminone-10 was favored over endocyclic enaminone-11 for 2-acetylcyclopentanone 2. 27 This was in line with the Dieckmann-Kon rule 23,24 where the endocyclic systems are favored over the exocyclic systems for reaction involving six-membered skeletons while the reversal is true for five-membered systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we had postulated the formation of enaminone (assisted by catalytic amounts of formic acid) that was generated in situ during the course of the photoreaction (Scheme 1), we independently synthesized the enaminone by thermal method. 27,28 Analysis of the enaminones derived from the thermal reaction of cyclic β-diketones 1/2 with o-vinlyanilines 3a-c showed that the endocyclic enaminone-8 was favored over exocyclic enaminone-9 for 2-acetylcyclohexanone 1, while the exocyclic enaminone-10 was favored over endocyclic enaminone-11 for 2-acetylcyclopentanone 2. 27 This was in line with the Dieckmann-Kon rule 23,24 where the endocyclic systems are favored over the exocyclic systems for reaction involving six-membered skeletons while the reversal is true for five-membered systems.…”
Section: Resultsmentioning
confidence: 99%
“…It was clear that there was a reversal in chemoselectivity when the diketone was changed from 2‐acetylcyclohexanone 1 to 2‐acetylcyclopentanone 2 , that is, the photoproduct featuring the vinylic methyl substituent was preferred in hexacyclic system (product 4 over 5 ), while the photoproduct featuring the bridge head methyl substituent was preferred in pentacyclic system (product 6 over 7 ). As we had postulated the formation of enaminone (assisted by catalytic amounts of formic acid) that was generated in situ during the course of the photoreaction (Scheme 1), we independently synthesized the enaminone by thermal method 27,28 . Analysis of the enaminones derived from the thermal reaction of cyclic β‐diketones 1 / 2 with o ‐vinlyanilines 3a‐c showed that the endocyclic enaminone‐ 8 was favored over exocyclic enaminone‐ 9 for 2‐acetylcyclohexanone 1 , while the exocyclic enaminone‐ 10 was favored over endocyclic enaminone‐ 11 for 2‐acetylcyclopentanone 2 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To complement the existing methodology, we aimed for a fuse – compress – expand sequence to 6,7‐dihydro‐cyclohepta[ b ]indol‐8(5 H )‐ones 4 that exploits an unprecedented photochemically triggered two‐carbon ring‐expansion (Figure ) . Fusing is accomplished by Sonogashira cross‐coupling between o ‐iodo anilines ( 5 ) and terminal alkynes ( 6 ), followed by condensation with five‐membered cyclic 1,3‐dicarbonyl compounds ( 7 ) and finalized by N ‐acylation to deliver photochemistry‐competent vinylogous amides 8 .…”
Section: Figurementioning
confidence: 99%
“…However, a thorough reaction-screening showed an exceptional example; the catalytic performance of the organoPCs was extremely different in DeMayo-type [2 + 2] cycloaddition [23][24][25][26][27][28][29] via EnT despite their similar excited energies. A showed an excellent catalytic e ciency for the reaction between methyl-2-(quinolin-2-yl)acetate (MQ) and styrene, whereas the tetracyclic variant B did not promote the same process well (Fig.…”
Section: Introductionmentioning
confidence: 99%